2020
DOI: 10.1002/qua.26443
|View full text |Cite
|
Sign up to set email alerts
|

Oriented external electric fields regulating the oxidation reaction of CH4 catalyzed by Mn‐corrolazine

Abstract: Mn-corrolazine-catalyzed CH 4 oxidation, as well as the regulation of its oriented external electric fields (OEEFs), is systematically studied using the first-principle calculations. Extensive density functional calculations show that the activation energy of CH 4 oxidation catalyzed by Mn-corrolazine is up to 38.5 kcal/mol in the field-free condition. However, when the OEEF is applied, the reactant and the transition state of the oxidation reaction are stabilized, originating from an attractive interaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Based on our previous research results, 48,49 the ground state of O-Fe-corrolazine is a quartet state, which exhibits excellent activation ability for the C-H bond in the methane oxidation to methanol reaction. Moreover, its catalytic ability can be regulated by OEEFs.…”
Section: The Propane Oxidation Catalyzed By O-fe-corrolazine In the A...mentioning
confidence: 96%
See 2 more Smart Citations
“…Based on our previous research results, 48,49 the ground state of O-Fe-corrolazine is a quartet state, which exhibits excellent activation ability for the C-H bond in the methane oxidation to methanol reaction. Moreover, its catalytic ability can be regulated by OEEFs.…”
Section: The Propane Oxidation Catalyzed By O-fe-corrolazine In the A...mentioning
confidence: 96%
“…Recently, our group reported that O-Fe-corrolazine can catalyze methane oxidation under mild conditions through the rebound mechanism and found that the reaction barrier can be effectively regulated by OEEFs. [48][49][50] As a novel kind of catalyst, OEEFs can effectively regulate various reactions through interactions with molecular dipole moments (D-M), which promotes or suppresses reactions, and can regulate regio-selectivity, stereo-selectivity, and spin selectivity. [51][52][53] Shaik et al conducted a lot of computational research on the effect of OEEFs on organic reactions [54][55][56][57][58] and found that organic reactions can be considerably promoted by OEEFs in the direction of the reaction axis, while regioselectivity and stereoselectivity can be modulated in other directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Fe(IV)-oxo porphyrin π-cation radical species, known as Cpd-I in heme proteins such as cytochrome P450, can mediate many key oxidative processes ( Meunier et al, 2004 ; Shaik et al, 2005 ; Cho et al, 2012 ; Zhang et al, 2017 ; Caddell Haatveit et al, 2019 ; Caulfield et al, 2019 ). Corrolazines, formed by replacing the meso-position carbon atoms of corroles with N atoms, are very similar in structure to porphyrins, but have more π electrons than porphyrins, and can better stabilize high-valent metals ( Ramdhanie et al, 2001 ; Goldberg et al, 2003 ; Fox et al, 2004 ; Lansky et al, 2005 ; Lansky and Goldberg, 2006 ; Goldberg 2007 ; McGown et al, 2009 ; Prokop et al, 2011 ; Pierloot et al, 2012 ; Baglia et al, 2015 ; Joslin et al, 2016 ; Jung et al, 2016 ; Zaragoza et al, 2016 ; Ghosh 2017 ; Zhu et al, 2018 ; Dedić et al, 2021 ; Wang et al, 2021 ; Zhu et al, 2021 ). As Fe is the active center metal of methane monooxygenase ( Shteinman 2020 ; Freakley et al, 2021 ), which can selectively convert methane to methanol under natural environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Strip out these reports, here, we tried a new strategy to reduce N 2 O with silanes via metal-free catalyst. It is known that oriented external electric field (OEEF) had been proved an effective, green, and controllable catalytic method, not only for the structures and properties of molecules, but also for the catalysis of chemical reactions [40][41][42][43][44][45][46][47][48]. In 2004, Shaik et al first reported that the OEEF could control the selectivity of iron-oxo porphyrin with propene [49].…”
mentioning
confidence: 99%